Pengaruh Security Privacy, Effort Expectancy, Performance Expectancy, Dan Social Influence Terhadap Behavioral Intention - Tuasikal, Mohammad Iqbal Ghifari; Prameka, Adelia Shabrina (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2024)
The growth of financial technology in payments provides significant benefits in transactions with ease and flexibility through digital scan barcode payments, especially in Indonesia. This study aims to examine the effect of  Security and Privacy, Effort Expectancy, Performance Expectancy, and Social Influence on Behavioral Intention in students using QRIS in Malang City. Quantitative research was conducted to examine the relationship between Security and Privacy, Effort Expectancy, Performance Expectancy, and Social Influence as independent variables and Behavioral Intention  as dependent variables  in this study. 122 students using QRIS in Malang were respondents in this study.  Multiple linear analysis was used as a data analysis technique in this study. Based on the results of data analysis, this study found that: 1) There is an influence of Security and Privacy on Behavioral Intention. The higher the level of security for using QRIS by students in Malang, the more likely they will intend to reuse payments with QRIS. 2) There is an effect of Effort Expectancy on Behavioral Intention. The easier it is to use QRIS for students in Malang, the higher the likelihood that they will intend to reuse payments with QRIS. 3) There is an influence between Social Influence and Behavioral Intention. The greater the influence of the surrounding environment, the higher the possibility of Behavioral Intention of students in Malang to reuse payments with QRIS.   Abstrak Pertumbuhan financial technology dalam pembayaran memberikan manfaat signifikan dalam transaksi dengan kemudahan dan fleksibilitas melalui pembayaran digital scan barcode, terutama di Indonesia. Penelitian ini bertujuan untuk menguji pengaruh Security and Privacy, Effort Expectancy, Performance Expectancy, dan Social Influence terhadap Behavioral Intention pada mahasiswa pengguna QRIS di Kota Malang. Penelitian kuantitatif dilakukan guna menguji hubungan antara Security and Privacy, Effort Expectancy, Performance Expectancy, dan Social Influence sebagai variable inedependen dan Behavioral Intention sebagai variable dependen dalam penelitian ini. 122 responden mahasiswa pengguna QRIS di kota Malang menjadi responden dalam penelitian ini. Analisis linier berganda digunakan sebagai teknik analisis data pada penelitian ini. Berdasarkan hasil analisis data penelitian ini menemukan bahwa: 1) Terdapat pengaruh Security and Privacy terhadap Behavioral Intention. Semakin tinggi tingkat keamanan penggunaan QRIS oleh mahasiswa di kota Malang, semakin meningkat kemungkinan mereka akan berniat menggunakan kembali pembayaran dengan QRIS. 2) Terdapat pengaruh Effort Expectancy terhadap Behavioral Intention. Semakin mudah penggunaan QRIS bagi mahasiswa di kota Malang, semakin tinggi kemungkinan mereka akan berniat menggunakan kembali pembayaran dengan QRIS. 3) Terdapat pengaruh antara Social Influence dan Behavioral Intention. Semakin besar pengaruh lingkungan sekitar, semakin tinggi kemungkinan Behavioral Intention mahasiswa di kota Malang untuk menggunakan kembali pembayaran dengan QRIS.